2022
DOI: 10.3389/fbioe.2022.915749
|View full text |Cite
|
Sign up to set email alerts
|

Study on the biological effects of ZnO nanosheets on EBL cells

Abstract: In this study, the biological effects of ZnO nanosheets were initially investigated using embryonic bovine lung (EBL) cells cultured in vitro as a model. ZnO nanosheets were prepared by a hydrothermal method, and their structure and morphology were characterized, and their effects on EBL cell viability, oxidative stress, cell proliferation, and apoptosis were investigated. The results showed that 12.5 μg ml−1 ZnO nanosheets can cause morphological changes in EBL cells. The toxic effects of ZnO nanosheets on EB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
2
1
0
Order By: Relevance
“…The structure observed was similar to that observed by Li et al. [41]. In undoped samples, stacking of the nanosheets was observed (Figures 4a and 4c), whereas in nitrogen‐doped samples, dispersed nanoflakes were found (Figures 4b and 4d).…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…The structure observed was similar to that observed by Li et al. [41]. In undoped samples, stacking of the nanosheets was observed (Figures 4a and 4c), whereas in nitrogen‐doped samples, dispersed nanoflakes were found (Figures 4b and 4d).…”
Section: Resultssupporting
confidence: 87%
“…The average diameter of the sheets was determined using ImageJ software and is found to have a sheet length of about 368 nm and 47 nm for ZnO and 344 nm and 53 nm for NÀ ZnO (calculated from Figures 4a and 4b, respectively). The structure observed was similar to that observed by Li et al [41]. In undoped samples, stacking of the nanosheets was observed (Figures 4a and 4c), whereas in nitrogen-doped samples, dispersed nanoflakes were found (Figures 4b and 4d).…”
Section: Characterization Of As Prepared Zno and Nà Znosupporting
confidence: 87%
See 1 more Smart Citation
“…Due to their water solubility, biocompatibility, low toxicity, and ease of modification, nanomaterials have been extensively researched for their potential to be combined with drugs. This combination aims to reduce side effects ( Li et al, 2020 ), improve drug efficacy ( Li et al, 2022 ), and enhance drug targeting ( Huang et al, 2019 ). For instance, a study reported the synthesis of highly biocompatible glycyrrhizic acid nanoparticles (GANPs) using glycyrrhizic acid (GA) as a raw material.…”
Section: Discussionmentioning
confidence: 99%